Peran Guru Pendidikan Agama Katolik Sebagai Gembala - Emanuel Haru (STIPAS St. Sirilus Ruteng, 2020)
Ruteng Diocese has launched 2020 as a pastoral year. This designation of a pastoral year is closely related to the pastoral focuses of previous years. Previously, a focus on pastoral care has been launched which includes four areas, namely sanctification (2016), proclamation (2017), fellowship (2018) and ministry (2019). These four focuses assume a leadership (shepherd) who is responsible for directing this pastoral care. Of course, the ordained shepherds, the bishop and priests, were responsible first. In addition, the participation of the people is also important. For the success or failure of these pastoral programs is dependent on the commitment and also good cooperation between ordained pastors and baptized pastors throughout the Ruteng Diocese. Catholic Religious Education Teacher is one of the many baptized pastors. He/ She is one of the components that has an important role in carrying out pastoral programs, especially in the field of education. A Catholic Religious Education Teacher is obliged to carry out the role of a shepherd in the sphere of education. The pastoral role of a Catholic Religious Education Teacher is based on the dignity of the sacrament of baptism and also by a special vocation as a pastoral officer who is specially prepared through education with a pastoral or catechetic background. In this article, the author emphasizes the role of a Catholic Religious Education Teacher as a school pastor in his capacity as a teacher/ educator. He/ She plays his/ her pastoral role in schools when teaching, guiding and motivating students and other faith formation activities in the context of implementing pastoral programs launched by the diocese. In carrying out the role of a baptized pastor, a Catholic Religious Education Teacher must have his own spirituality. And the spirituality of the shepherding of a Catholic Religious Education Teacher comes from Jesus himself as the True Shepherd. By being guided by the spirituality of pastoral originating from Jesus the true Shepherd, it is hoped that a Catholic Religious Education Teacher will be able to carry out his/ her pastoral mission well in the school.